Financial expense incurred by medical leaves of health professionals in Rondonia public hospitals, Brazil El gasto financiero causado por las licencias médicas de profesionales de la salud en los hospitales públicos en Rondonia, Brasil Gasto financeiro ocasionado pelos atestados médicos de profissionais da saúde em hospitais públicos no Estado de Rondônia, Brasil - Maria Bernadete Junkes; Valdir Filgueiras Pessoa (Universidade de São Paulo, 2010)
The study investigates the additional payroll expense caused by absenteeism due to illness among nursing professionals and physicians at two public hospitals at Cacoal, Rondonia, Brazil. Non-programmed absences of up to 15 days which occurred at the hospital units between 2004 to 2007 were verified in the database of the institutions' human resource sector. From 1,704 non-programmed absences, 1,486 were justified by medical declarations. It was verified that absenteeism caused by illness was responsible for 87.2% of all non-programmed absences. When these data are grouped by professional categories, it was observed that the nurse absenteeism due to illness reached 83.3%, when compared with 16.7% for physicians. The general absenteeism index, adding up nurses and physicians, corresponded to 0.85%, resulting in an additional payroll expense of 5.2% and 7.4% in the salaries of nursing professionals and physicians, respectively. El objetivo de este estudio fue investigar el gasto adicional en la planilla de pago, causado por el absentismo enfermedad de profesionales de enfermería y médicos, en dos hospitales públicos de la ciudad de Cacoal, en Rondonia, Brasil. Fueron verificadas ausencias no programadas de hasta 15 días en las unidades hospitalarias, en el período de 2004 a 2007, constatadas en el banco de datos del sector de recursos humanos de las instituciones. Se constató 1.704 ausencias no programadas, de las cuales 1.486 son justificadas con certificados médicos. Se verificó que el absentismo por motivo de enfermedad fue responsable por 87,2% de las ausencias no programadas. Si fuese descrito por categoría profesional, el absentismo enfermedad de los profesionales de enfermería alcanzaría el índice de 83,3% y el de los médicos 16,7%. El índice de absentismo general de los profesionales de enfermería y médicos fue de 0,85%, en cuanto que el gasto adicional en la planilla de pago en el período alcanzó 5,2% en los salarios de los profesionales de enfermería y 7,4% de los médicos. O objetivo deste estudo foi investigar o gasto adicional na folha de pagamento, causado pelo absenteísmo doença de profissionais de enfermagem e médicos, em dois hospitais públicos da cidade de Cacoal, Rondônia, Brasil. Foram verificadas ausências não programadas de até 15 dias nas unidades hospitalares, no período de 2004 a 2007, observadas no banco de dados do setor de recursos humanos das instituições. Constatou-se 1.704 ausências não programadas, das quais 1.486 são justificadas por atestados médicos. Verificou-se que o absenteísmo por motivo de doença foi responsável por 87,2% das ausências não programadas. Se for descrito por categoria de profissional, o absenteísmo doença dos profissionais de enfermagem atingiu índice de 83,3% e dos médicos 16,7%. O índice do absenteísmo geral dos profissionais de enfermagem e médicos foi de 0,85%, enquanto que o gasto adicional na folha de pagamento no período atingiu 5,2% nos vencimentos dos profissionais de enfermagem e 7,4% dos médicos.